Development of science-environmental movement relationships: The case of Russia (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
There is a paradoxical situation in the world: after the end of the WWII the science took leading position in all spheres of human activity but there was no any fundamental research on science-environmental movement relationships. Recently, Russian science in public life exists in two major forms. First in the form of manifestos like the Pugwash Manifesto  in the year of 1955 (Butcher, 2005) which resulted in long-term numerous gatherings, discussions and appeals to world community and the second in the form of scientists-turned-civil activists who consciously left their positions in research institutes and entered an environmental and other social movements. The following text is based on the empirical study of the above relationships from the early 1900s till now in its widest sense (i.e. including charity, justice, peaceful and other forms of civil activism). The major forms of this activism were as follows: the writing the programs of alterative development of science, industry and agriculture; a work as the tutors of the studentsâ€™ nature protection movement; the participation in the work of the committees on civil rights and freedoms; the establishment of alternative units of experts and advisers for public hearings, etc. In the run of this long-term period the situation is turned upside down: those who were students have become the scientifically-sound leaders of complex interdisciplinary movements without boundaries who actively participate in global transnational projects with global stakeholders on equal ground. It gives me the grounds to speak on the emergence of a new format of science-social movement relationships. The author suggests a hypothesis that the researchers of current environmental movements are needed in an integrated socio-bio-technical paradigm of actor-subject matter development.